Factors influencing employee job satisfaction in Ghana's hotel industry. Issue 2 (2nd April 2016) - Amissah, Eunice Fay; Gamor, Emmanuel; Deri, Mildred Nuong; Amissah, Agnes
ABSTRACT: This study examined factors affecting job satisfaction and also assessed the level of satisfaction of employees working in the hotel industry. The study gathered descriptive data using questionnaires from 190 hotel employees. Factor analysis was employed to extract job satisfaction factors while the standard multiple regression was used to analyze the predictive factors of job satisfaction. The results showed that employees were slightly satisfied with their jobs. The study also identified four main facets of satisfaction, namely pay, supervision, promotion, as well as training and advancement. Of these factors, pay, supervision, and promotion were found to significantly influence job satisfaction. Managerial implications are that hotel managers can overcome employee dissatisfaction by providing employees with competitive pay and also by training supervisors on the use of good communication, among other techniques.